Parental Perceptions of Obesity and Obesity Risk Associated With Childhood Acute Lymphoblastic Leukemia. Issue 5 (July 2017) - Jones, Gary L.; McClellan, Wendy; Raman, Sripriya; Sherman, Ashley; Guest, Erin; August, Keith
Abstract : The prevalence of obesity and related comorbidities in survivors of childhood acute lymphoblastic leukemia (ALL) is well established and ranges anywhere from 29% to 69% depending on the study. We sought to explore the awareness of parents of survivors of childhood ALL regarding the increased risk of obesity and their perceptions regarding the overall health of their child. One hundred twenty-one parents of 99 survivors of pediatric ALL completed surveys regarding perceptions of obesity risk in survivors. Eighty percent of parents of overweight and obese survivors correctly identified their child as "a little overweight" or "overweight." Few parents recalled discussing weight gain (21%) or obesity risk (36%) with their practitioner. Parents that did recall having these discussions and/or reported a decreased level of posttherapy activity in their child were more likely to be concerned about their child's weight status. Improved awareness and education regarding the risk of obesity and associated comorbid conditions may provide an avenue for future prevention of obesity in survivors of pediatric ALL. Discussion and education regarding a healthy lifestyle, including proper diet and exercise, should be incorporated early in routine patient visits. Abstract : Supplemental Digital Content is available in the text.